Foamed concrete phase change particles and preparation method and application thereof

By preparing foam concrete phase-change particles and evenly distributing the phase-change material inside the particles, the poor compatibility and leakage problems when traditional building materials are combined with phase-change materials are solved, and good thermal insulation and heat storage functions and stability of phase-change building materials are achieved.

CN116969776BActive Publication Date: 2025-04-15QINGHAI INST OF SALT LAKES OF CHINESE ACAD OF SCI
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310889900.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-07-19
Publication Date
2025-04-15
Estimated Expiration
2043-07-19

AI Technical Summary

Technical Problem

When traditional building materials are combined with phase change building materials, phase change materials are prone to leakage, resulting in failure after long-term use.

Method used

The preparation method of foam concrete phase change particles is adopted. By adding foam to the slurry, it solidifies into foam concrete, crushes into particles, and forms communication holes in the solvent, and then immerses in the phase change solution to make the phase change material evenly distributed inside the particles.

Benefits of technology

The formed phase-change building materials have good thermal insulation and heat storage functions, and the phase-change materials are distributed evenly to prevent leakage, improving the stability of the material and the reliability of long-term use.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116969776B_ABST
    Figure CN116969776B_ABST
Patent Text Reader

Abstract

The present invention discloses a foam concrete phase change particle and a preparation method and application thereof. The method comprises adding foam to the slurry, mixing, solidifying into foam concrete, crushing the foam concrete and soaking it in a solvent to form interconnected pores inside to obtain porous particles, immersing the particles in a phase change solution to form foam concrete phase change particles, and then mixing with other building materials and injecting them into a mold for curing to form phase change building materials. The foam concrete phase change particles prepared by the present invention form interconnected pores inside, so that the phase change material is evenly distributed, and can effectively prevent the leakage of the phase change material; the prepared phase change building material has low thermal conductivity, has good thermal insulation and heat storage functions, has a simple preparation process, and is low in cost; the phase change material and packaging material formed by the same material make the phase change building material have good workability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of building materials, and in particular relates to foam concrete phase-change particles and a preparation method and application thereof. Background Art

[0002] Phase change materials are phase change materials in wall materials that undergo a phase change at a specific temperature, accompanied by heat absorption or heat release, and use the heat stored in latent heat to regulate indoor temperature. Applying phase change materials to building envelopes can solve the problem of low heat capacity of ordinary lightweight materials used in modern buildings, increase the heat storage capacity and thermal inertia of building envelopes, and due to the large latent heat of phase change materials, a small amount of phase change materials can store a large amount of heat, while also reducing the temperature variation range of indoor and outdoor buildings, playing a certain role in reducing the heat and cold load of air conditioning system design, and achieving energy saving and improving thermal comfort. In the field of building energy conservation, the selection of phase change materials is crucial. Starting from reality, and selecting from the thermal physical characteristics of phase change materials and economic aspects, the best heat storage effect of phase change materials should be achieved, and the price should be low and easy to promote.

[0003] Phase change energy storage materials are generally difficult to use directly when used as building materials. In most cases, they need to be formed into solid or non-leaking composite materials. The current application methods of phase change energy storage materials in construction include: ① Directly immersing the phase change material into the pores of building materials or incorporating it into building materials as fillers. ② Preparing the phase change material into a fixed-shape phase change material or encapsulating it into a monomer and then combining it with the building material. The first method is simple to operate, but the surface of the component is prone to obvious leakage during the phase change process, and the safety and stability are poor, which is not conducive to long-term use. The second method avoids direct contact between the phase change material and traditional building materials, can effectively realize latent heat storage and improve the stability of the application, but the production process of the fixed-shape phase change material or encapsulation into a monomer is relatively complicated, considering the packaging cost, operating process, economy and batch use cannot be guaranteed.

[0004] Directly infiltrating or incorporating phase change energy storage materials into building materials is the focus of future development because it is simple, economical and can play an effective role. Especially with the increasing requirements for building energy conservation and sustainable development, this method is highly operable in different occasions and the design requirements for building components can be easily achieved. At present, phase change materials can be divided into inorganic, organic and composite phase change materials according to their chemical composition. Inorganic phase change materials are the most widely used inorganic phase change materials and are also typical solid-liquid phase change materials. Compared with organic phase change materials, they are widely available and inexpensive, have no irritating odor, and have stable chemical properties, making them more suitable for application in the field of building energy conservation. However, inorganic phase change materials have the defects of supercooling and phase separation, and their application is limited. Secondly, most inorganic phase change materials are hydrated salts. Combining with traditional building materials will not only cause direct leakage problems, but also corrode the base material for long-term use, leading to leakage or failure.

[0005] Therefore, there is an urgent need to provide a method for preparing a phase change building material to solve these problems. Summary of the invention

[0006] The invention provides a foam concrete phase change particle and a preparation method and application thereof, aiming to solve the problems of poor compatibility between traditional building materials and phase change building materials, easy leakage of phase change materials and failure due to long-term use.

[0007] In order to achieve the above technical effects, the present invention adopts the following technical solutions:

[0008] The present invention provides a method for preparing foamed concrete phase-change particles, comprising: adding foam to slurry and mixing to solidify into foamed concrete, crushing the foamed concrete into foamed concrete particles, immersing the foamed concrete particles in a solvent to form interconnected pores inside to obtain pore-forming particles, immersing the pore-forming particles in a phase-change solution so that the phase-change solution is evenly distributed in the interconnected pores to form the foamed concrete phase-change particles.

[0009] Furthermore, the slurry includes any one of MOC slurry and MOS slurry.

[0010] Furthermore, the foam is prepared by any one of physical foaming and inorganic foaming.

[0011] Furthermore, the MOC slurry is prepared by mixing a magnesium chloride solution with active magnesium oxide.

[0012] Furthermore, the MOS slurry is formed by mixing a magnesium sulfate solution and active magnesium oxide.

[0013] Furthermore, the curing process includes drying at 25° C. for 3-7 days or drying at 30-80° C. for 3-24 hours.

[0014] Furthermore, the activity of the activated magnesium oxide is between 20% and 80%.

[0015] Furthermore, the foamed concrete particles are immersed in the solvent for 5-7 days to obtain porous particles.

[0016] Furthermore, the MOC slurry is prepared by mixing a magnesium chloride solution having a concentration of 15%-30% and active magnesium oxide in a mass ratio of 0.5-1.2:1.

[0017] Furthermore, the MOS slurry is prepared by mixing a magnesium sulfate solution having a concentration of 15%-30% and active magnesium oxide in a mass ratio of 0.5-1.2:1.

[0018] Furthermore, when the slurry is MOC slurry, the solvent includes any one of water, a magnesium chloride solution with a concentration less than 25%, or alcohol.

[0019] Furthermore, when the slurry is MOS slurry, the solvent includes any one of water, magnesium sulfate solution with a concentration less than 25%, or alcohol.

[0020] Furthermore, the phase change material includes any one of a magnesium sulfate solution, a magnesium chloride solution, and a mixed solution of calcium chloride and magnesium chloride.

[0021] Foamed concrete phase-change particles prepared by the preparation method provided by the invention.

[0022] The present invention also provides a phase-change building material, which comprises mixing the above-mentioned foam concrete phase-change particles with active magnesium oxide powder, magnesium chloride solution or magnesium sulfate solution to form assembled concrete, and then curing to form the phase-change building material.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] 1. Forming a porous material that does not react with the phase change material makes the phase change material evenly distributed, effectively preventing the leakage of the phase change material, reducing the thermal conductivity, and having good thermal insulation and heat storage functions.

[0025] 2. The cementitious material is consistent with the phase change material and the packaging material, which makes the phase change building material have good workability. The same materials are more conducive to forming a whole, improving the supercooling and phase separation problems of the phase change material.

[0026] 3. The present invention first forms particles with holes inside, then introduces phase change materials into the holes formed inside the particles, and then forms the assembled concrete. It combines the advantages of the direct incorporation method and the encapsulation method, so that the phase change material distribution inside the formed assembled concrete is more uniform, which is beneficial to reducing thermal conductivity. The preparation process is simple and easy to promote, and the economic cost is low. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0028] Figure 1 It is a schematic diagram of forming interconnected pores inside pore-forming particles in Example 1 of the present application.

[0029] Figure 2 It is a schematic diagram of forming pores inside MOC foam concrete in Example 1 of the present application. DETAILED DESCRIPTION

[0030] The present invention will be more fully understood through the following detailed description, which should be read in conjunction with the accompanying drawings. Detailed embodiments of the present invention are disclosed herein; however, it should be understood that the disclosed embodiments are only exemplary of the present invention, which can be embodied in various forms. Therefore, the specific functional details disclosed herein should not be interpreted as limiting, but only as the basis of the claims and as a representative basis for teaching those skilled in the art to adopt the present invention in different ways in virtually any appropriate detailed embodiment.

[0031] Example 1

[0032] This embodiment provides a foamed concrete phase change particle. Specifically, the preparation method includes:

[0033] 1. Dissolve magnesium chloride in water to prepare a 25% MgCl2 solution, and mix it with active magnesium oxide powder (activity 60%) at a mass ratio of 0.5:1 and stir to form MOC slurry.

[0034] 2. The foam prepared by the physical foaming agent is mixed into the above MOC slurry and mixed evenly, and dried at 25°C for 7 days for curing, and pores are formed at the original location of the foam to obtain MOC foam concrete.

[0035] See also Figure 2 , is a schematic diagram of forming pores inside the MOC foam concrete in this embodiment.

[0036] 3. The MOC foamed concrete is crushed to obtain MOC foamed concrete particles, and particles of 0.5-5 cm are screened out.

[0037] 4. Soak the above particles with a particle size of 1-2 cm in a 15% magnesium chloride solution for 5 days. MOC will be hydrated and decomposed in a water environment. After soaking, the weak areas of the pore wall are hydrated and decomposed to make the internal pores interconnected to form interconnected holes inside, thereby obtaining porous particles, that is, the packaging material for encapsulating the phase change solution.

[0038] See also Figure 1 , it can be seen that the pore walls inside the pore-forming particles are interconnected to form interconnected pores.

[0039] 5. The pore-forming particles are immersed in a mixed phase change solution of calcium chloride (CaCl2·6H2O) and magnesium chloride (MgCl2·6H2O) so that the interconnected pores inside the pore-forming particles are filled with the phase change material to form X-MOC foam concrete phase change particles containing the phase change material.

[0040] 6. Dry the X-MOC foamed concrete phase change particles at 50°C.

[0041] 7. Dissolve magnesium chloride in water to prepare a 25% MgCl2 solution and mix it with the active magnesium oxide powder, the X-MOC foam concrete phase change particles and other screened MOC foam concrete particles (with particle sizes of 0.5-1 cm and 2-5 cm) to form MOC aggregate concrete.

[0042] 8. The MOC mixed concrete is uniformly mixed and poured into the mold, and cured at room temperature for 7 days to form a phase change building material of designed size.

[0043] The phase change material contains magnesium chloride, which forms MOC slurry with active magnesium oxide to solidify into concrete, and then is broken into MOC foam concrete particles (i.e., packaging material). The foam concrete phase change particles are mixed with magnesium chloride and other materials for curing to form phase change building materials. This phase change building material with the same cementitious material, phase change material and packaging material as the phase change building material has good workability, and similar materials are more conducive to forming a whole, thereby improving the supercooling and phase separation problems of the phase change material.

[0044] Example 2

[0045] This embodiment provides a foamed concrete phase change particle. Specifically, the preparation method includes:

[0046] 1. Dissolve magnesium sulfate in water to prepare a magnesium sulfate solution with a concentration of 25%, and mix it with active magnesium oxide powder (activity 60%) at a mass ratio of 1.2:1 and stir to form MOS slurry.

[0047] 2. The foam made by the physical foaming agent is mixed into the above MOS slurry and mixed evenly, and dried at 80°C for 24 hours to form pores at the original location of the foam to obtain MOS foam concrete.

[0048] 3. The MOS foam concrete is crushed to obtain MOS foam concrete particles, and MOS foam concrete particles of 0.5-5 cm are screened out.

[0049] 4. The MOS foam concrete particles with a particle size of 1-2 cm are soaked in water for 7 days. MOS will be hydrated and decomposed in the water environment. After soaking, the weak areas of the pore wall are hydrated and decomposed so that the internal pores are interconnected to form interconnected pores inside to obtain porous particles.

[0050] 5. Immerse the above-mentioned pore-forming particles in a Na2SO4·10H2O phase change solution so that the internal interconnected pores are filled with the phase change material to form X-MOS foam concrete phase change particles containing the phase change material.

[0051] 6. Dry the X-MOS foam concrete phase change particles at 50°C.

[0052] 7. Dissolve magnesium sulfate in water to prepare a magnesium sulfate solution with a concentration of 25%, and mix it with active magnesium oxide powder, X-MOS foam concrete phase change particles and other MOS foam concrete particles (with particle sizes of 0.5-1 cm and 2-5 cm) to form MOS assembled concrete.

[0053] 8. The MOS mixed concrete is uniformly mixed and poured into a mold, and cured at room temperature for 14 days to form phase change building materials of different sizes.

[0054] Example 3

[0055] The only difference between Example 3 and Example 1 is that in step (4) of Example 3, the MOC foam concrete particles are immersed in a magnesium chloride solution with a concentration of 24% for 7 days, and the other conditions remain the same as those of Example 1.

[0056] Example 4

[0057] The only difference between this embodiment and embodiment 1 is that the MOC slurry is prepared by mixing a 15% magnesium chloride solution and active magnesium oxide in a mass ratio of 1.2:1. The other conditions are the same as those in embodiment 1.

[0058] Example 5

[0059] The only difference between this embodiment and embodiment 1 is that the MOC slurry is prepared by mixing a 30% magnesium chloride solution and active magnesium oxide at a mass ratio of 0.8:1. The other conditions are the same as those in embodiment 1.

[0060] Example 6

[0061] The only difference between this embodiment and embodiment 2 is that the MOS slurry is prepared by mixing a 15% magnesium sulfate solution and active magnesium oxide at a mass ratio of 0.5:1. The other conditions are the same as those in embodiment 2.

[0062] Example 7

[0063] The only difference between this embodiment and embodiment 2 is that the MOS slurry is prepared by mixing a 30% magnesium sulfate solution and active magnesium oxide at a mass ratio of 0.8:1. The other conditions are the same as those in embodiment 2.

[0064] Example 8

[0065] The only difference between this embodiment and embodiment 1 is that the activity of the active magnesium oxide in this embodiment is 20%. The other conditions are the same as those in embodiment 1.

[0066] Example 9

[0067] The only difference between this embodiment and embodiment 1 is that the activity of the active magnesium oxide in this embodiment is 80%. The other conditions are the same as those in embodiment 1.

[0068] Example 10

[0069] The only difference between this embodiment and embodiment 1 is that the MOC foam concrete particles are soaked in alcohol for 7 days, and the other conditions are consistent with those in embodiment 1.

[0070] Embodiment 11

[0071] The only difference between this embodiment and the embodiment 1 is that the foam is mixed with the MOC slurry and then dried at 25° C. for 3 days for curing. The other conditions are consistent with those of embodiment 1.

[0072] Example 12

[0073] The only difference between this embodiment and embodiment 2 is that in this embodiment, the MOS slurry and foam are mixed and dried at 30° C. for 3 hours, and the other conditions are the same as those in embodiment 2.

[0074] Comparative Example 1

[0075] The only difference between Comparative Example 1 and Example 1 is that in Comparative Example 1, no foam pores are added, and the phase change material is directly added to the MOC slurry. The other conditions remain the same as in Example 1.

[0076] The phase change building materials prepared in Example 1 and Comparative Example 1 were subjected to performance tests using a multi-point heat flow meter. The test results are as follows:

[0077] The thermal conductivity of the phase change building material prepared in Example 1 and the phase change building material prepared in Comparative Example 1 are compared, as shown in Table 1 below. The thermal conductivity of the phase change building material prepared in Example 1 is significantly lower than that of the phase change building material prepared in Comparative Example 1. The phase change building material prepared in Example 1 has better thermal insulation and heat storage functions.

[0078] Table 1 Comparison of thermal conductivity of phase change building materials obtained in Example 1 and Comparative Example 1

[0079] name Thermal conductivity (W / mk) Example 1 0.1188 Comparative Example 1 0.1360

[0080] The workability and 28d compressive strength of Example 1, Comparative Example 1 and ordinary Portland cement system building materials are compared, as shown in Table 2 below. The cementitious material in Example 1 is consistent with the phase change material and the packaging material, so that the phase change building material has good workability, and similar materials are more conducive to forming a whole, improving the supercooling and phase separation problems of the phase change material, and at the same time obtaining better mechanical properties.

[0081] Table 2 Comparison of mechanical properties of Example 1, Comparative Example 1 and ordinary Portland cement series phase change building materials

[0082]

[0083] The present invention forms pores inside the concrete by adding porous foam into the slurry, and then immerses the slurry in a corresponding solvent so that the pore walls between the pores are decomposed and connected to form connected pores, and then immerses the slurry in a phase change material so that the connected pores formed inside are evenly distributed with the phase change material, and are not prone to leakage and will not fail over time. Compared with other capsule methods, the cementitious material and the phase change material in the present invention are consistent, so that the finally formed phase change building material has good workability and is more conducive to forming a whole. The method for preparing the phase change building material of the present invention can be regarded as a combination of direct infiltration and encapsulation, which reduces the thermal conductivity, so that the phase change building material has good thermal insulation and heat storage functions, and the preparation process is simple and has strong scalability.

[0084] It should be noted that the phase change building material in the present invention is not exclusive but exemplary, and other common phase change materials can be replaced.

[0085] Although the present invention has been described with reference to illustrative embodiments, it will be appreciated by those skilled in the art that various other changes, omissions and / or additions may be made and that elements of the described embodiments may be substituted with substantial equivalents without departing from the spirit and scope of the present invention. In addition, many modifications may be made to adapt a particular situation or material to the teachings of the present invention without departing from the scope of the present invention. Therefore, it is not intended herein to limit the present invention to the specific disclosed embodiments for carrying out the present invention, but rather it is intended that the present invention will include all embodiments within the scope of the appended claims.

Claims

1. A method for preparing foamed concrete phase change particles, characterized in that include: Adding foam to the slurry and mixing to solidify into foamed concrete, breaking the foamed concrete into foamed concrete particles, soaking the foamed concrete particles in a solvent for 5-7 days to form interconnected pores inside to obtain pore-forming particles, and immersing the pore-forming particles in a phase change solution so that the phase change solution is evenly distributed in the interconnected pores to form the foamed concrete phase change particles; The slurry is any one of MOC slurry and MOS slurry; the MOC slurry is formed by mixing a magnesium chloride solution with a concentration of 15%-30% and active magnesium oxide at a mass ratio of 0.5-1.2:1; the MOS slurry is formed by mixing a magnesium sulfate solution with a concentration of 15%-30% and active magnesium oxide at a mass ratio of 0.5-1.2:1; When the slurry is MOC slurry, the solvent is any one of water, magnesium chloride solution with a concentration less than 25%, or alcohol; When the slurry is MOS slurry, the solvent is any one of water, magnesium sulfate solution with a concentration less than 25%, or alcohol; The phase change solution is any one of a magnesium sulfate solution, a magnesium chloride solution, and a mixed solution of calcium chloride and magnesium chloride.

2. The method for preparing foamed concrete phase change particles according to claim 1, characterized in that: The foam is prepared by any one of physical foaming and inorganic foaming.

3. The method for preparing foamed concrete phase change particles according to claim 1, characterized in that: The curing process includes drying at 25°C for 3-7 days or drying at 30-80°C for 3-24 hours; The activity of the activated magnesium oxide is between 20% and 80%.

4. Foamed concrete phase-change particles prepared by the method for preparing foamed concrete phase-change particles according to any one of claims 1 to 3.

5. A phase change building material, characterized in that: The method comprises mixing the foamed concrete phase change particles described in claim 4 with active magnesium oxide powder and magnesium chloride solution to form assembled concrete, and curing the concrete to form the phase change building material; or mixing the foamed concrete phase change particles described in claim 4 with active magnesium oxide powder and magnesium sulfate solution to form assembled concrete, and curing the concrete to form the phase change building material.

6. Use of the foamed concrete phase-change particles according to claim 4 or the phase-change building materials according to claim 5 in the field of construction.

Citation Information

Patent Citations

  • Magnesium cement phase change building material and preparation method thereof

    CN111004011A